Planes

Geometry Level 3

Consider the represented planes:

α \alpha : b 2 x + y + z = b x { b }^{ 2 }x+y+z=bx

β \beta : 2 x + y = 2 z 2x+y=-2-z

γ \gamma : x + b ( y + z ) = 0 x+b(y+z)=0

b R b \in \mathbb{R} \diagdown {0}

\cdot α \alpha and β \beta are strictly parallel.

\cdot γ \gamma intersects α \alpha and β \beta , but it isn't perpendicular to them.

What is the value of b b ?


This problem was created by José Carlos Pereira
1 3 2 -1

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

α \alpha : b 2 x + y + z = b x { b }^{ 2 }x+y+z=bx \leftrightarrow ( b 2 b ) x + y + z = 0 ({ b }^{ 2 }-b)x+y+z=0

β \beta : 2 x + y = 2 z 2x+y=-2-z \leftrightarrow 2 x + y + z = 2 2x+y+z=-2

γ \gamma : x + b ( y + z ) = 0 x+b(y+z)=0 \leftrightarrow x + b y + b z = 0 x+by+bz=0

If α \alpha and β \beta are strictly parallel, their normal vectors are colinear.

n α \vec{{n}_{\alpha}} : ( b 2 b , 1 , 1 ) ({ b }^{ 2 }-b,\quad 1,\quad 1)

n β \vec{{n}_{\beta}} : ( 2 , 1 , 1 ) (2,\quad 1,\quad 1)

k R : n α = k n β \exists k \in \mathbb{R}: \vec{{n}_{\alpha}}=k\vec{{n}_{\beta}} \leftrightarrow ( b 2 b , 1 , 1 ) = k ( 2 , 1 , 1 ) ({ b }^{ 2 }-b,\quad 1,\quad 1)=k(2,\quad 1,\quad 1) \leftrightarrow k = 1 b 2 b = 2 k k=1 \wedge { b }^{ 2 }-b=2k \rightarrow b = 1 b = 2 b=-1 \vee b=2 .

If γ \gamma isn't perpendicular to β \beta and γ \gamma :

n α n γ 0 n β n γ 0 \vec{{n}_{\alpha}} \cdot \vec{{n}_{\gamma}} \neq 0 \wedge \vec{{n}_{\beta}} \cdot \vec{{n}_{\gamma}} \neq 0

n γ : ( 1 , b , b ) \vec{{n}_{\gamma}}:(1,\quad b, \quad b)

n α n γ = 0 ( b 2 b , 1 , 1 ) ( 1 , b , b ) b 2 + b = 0 b = 0 b = 1 \vec{{n}_{\alpha}} \cdot \vec{{n}_{\gamma}} = 0 \leftrightarrow ({ b }^{ 2 }-b,\quad 1,\quad 1) \cdot (1,\quad b, \quad b) \leftrightarrow { b }^{ 2 }+b=0 \leftrightarrow b=0 \vee b=-1

n β n γ = 0 ( 2 , 1 , 1 ) ( 1 , b , b ) = 0 2 + 2 b = 0 b = 1 \vec{{n}_{\beta}} \cdot \vec{{n}_{\gamma}} = 0 \leftrightarrow (2,\quad 1,\quad 1) \cdot (1,\quad b, \quad b) = 0 \leftrightarrow 2+2b=0 \leftrightarrow b=-1

T h e n , b 1 b 0 Then, \quad b\neq -1 \wedge b\neq 0

b = 2 \therefore b=2

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...